Perlindungan Hukum Pekerja di Bidang Jaminan Sosial Tenaga Kerja Pasca Berlakunya PERPU Cipta Kerja - Dede Agus (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2023)
The safeguarding of laborers and workers' rights within the framework of social security has evolved through various legislative phases, originating from the Dutch colonial era and culminating in the recent enactment of the Job Creation Perpu No. 2 of 2022. This paper aims to scrutinize the legal protection afforded to laborers in the realm of social security following the implementation of the Job Creation Perpu. Employing normative juridical methods and utilizing statute and conceptual approaches, this research leverages secondary data and qualitative descriptive analysis to explore solutions to legal quandaries. The study reveals that the Job Creation Perpu has modified and updated provisions pertaining to workers' social security within Law No. 40 of 2004 on the National Social Security System and Law No. 24 of 2011 on Organizers of the Social Security Bodies. Consequently, the social security framework now encompasses six distinct programs: health insurance, work accident insurance, old age insurance, pension insurance, death insurance, and job loss insurance. The addition of job loss insurance as a supplementary program enriches social security for workers by offering cash benefits, access to labor market information, and job training to those experiencing layoffs. This comprehensive approach enhances the protection of workers against socio-economic risks within the ambit of social security.